A közszférából történő munkaerő-kiáramlás elemzése Magyarországon - Péter Elek; Péter András Szabó (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– Based on the microbased panel datasets of the Labour Force Survey between 1998 and 2010 and the administrative Pension Fund data between 2000 and 2006 we analyse the number, composition and subsequent labour market behaviour of former public sector employees in Hungary. We show that the greater stability of the public sector stems from the fact that the transition probabilities from it to unemployment and to other economic branches / occupations are both about half of the corresponding probabilities from the public sector. Meanwhile, the exit probabilities to inactivity do not differ substantially between the two sectors. By analysing the reemployment probabilities of the laid-off workers with Jenkins' discrete time hazard model we find that those who lost their jobs in the public sector find a new job with a 5-25 percent smaller intensity - i.e. by 5-25 percent more slowly - than their private sector counterparts. However, this difference disappears among the higher educated. Finally, after controlling for education, those who leave the public sector for the private sector do not become overeducated in their new job with a significantly higher probability than similar workers switching jobs within the private sector.
Keywords: C41; J45; J62; J64; 330; labour market of the public sector; labour market transition probabilities; unemployment duration; Jenkins discrete time hazard model; Öffentlicher Dienst; Arbeitsmobilität; Arbeitslosigkeit; Qualitative Methode; Statistische Bestandsanalyse; Panel; Ungarn